PENINGKATAN LITERASI KEUANGAN ISLAM TERINTEGRASI DIGITAL FINANCE BAGI GURU TK AISYIYAH KECAMATAN CANDI: STRENGTHENING ISLAMIC FINANCIAL LITERACY INTEGRATED WITH DIGITAL FINANCE FOR AISYIYAH KINDERGARTEN TEACHERS - Ima Faizah; Ninda Ardiani; Eva Hidayatul Kusnah (LPPM Universitas Abdurrab, 2025)
The advancement of digital technology demands enhanced Islamic financial literacy, especially for Aisyiyah kindergarten teachers, to support financial management in accordance with Sharia principles. This program aims to equip participants with knowledge and skills in financial management through digital finance-based training. The training materials include an introduction to basic Islamic finance concepts, Sharia-based family budgeting, the use of Sharia-compliant e-wallets, halal investment options, and data protection and digital transaction security. A participatory approach was applied through pre-tests, interactive training sessions, and post-tests. To assess the program's effectiveness, data analysis employed a quantitative approach by comparing pre-test and post-test results, alongside qualitative methods through interviews and observations conducted during the training. The program results indicated a 57% increase in participants' understanding, with 65% starting to develop Sharia-based budgets and 60% reducing the use of consumptive credit. Major challenges include participants' limited familiarity with Sharia-based digital financial services and fewer features compared to conventional services. Continuous mentoring is necessary to ensure the optimal implementation of Sharia financial principles. This program contributes to strengthening Sharia-based financial independence among Aisyiyah kindergarten teachers, who are expected to share this understanding within their schools and communities.